Is knowledge power? Knowledge flows, subsidiary power and rent-seeking within MNCs - Mudambi, Ram; Navarra, Pietro (Journal of International Business Studies, 2004)
In recent years, as multinational corporation (MNC) subsidiaries have become more closely linked to international networks, their knowledge intensity has risen, and some of their R&D has gained a more creative role. Simultaneously, and often connectedly, many subsidiaries have acquired considerable strategic independence in all aspects of their operations, and therefore are able to exercise considerable intra-firm bargaining power to influence the distribution of the firm's resources. In this context, we suggest that intra-MNC knowledge flows are a key determinant of subsidiary bargaining power. We argue that subsidiary managers can exploit such power to pursue their own ends. Such rent-seeking behavior is implicit in much of the literature on managerialism, but our analysis suggests that such behavior can now occur in headquarters–subsidiary and subsidiary–subsidiary relations. Thus subsidiary strategic independence, designed to enhance the competitiveness of outputs (market knowledge) and inputs (asset-seeking and learning), can be corroded when the pursuit of subsidiary objectives encourages rent-seeking. Empirical analysis of a sample of high-technology subsidiaries in the UK provides strong support for the theory. We examine several avenues whereby the incentives of units within the MNC can be aligned.